“Modelos pedagógicos tradicional y constructivista en el proceso de aprendizaje” - Toctaguano Toapanta, Hilda Janeth (2022)
In nowadays, education requires new ways of teaching and learning, because new generations emerge with different educative demands which have to be resolved for a good integral development. On the other side, in XXI century, teachers must know each pedagogical models and their characteristics in order to apply an appropriate model. In the presence of this, the development of the different elements of the teaching and learning process respond to the traditional pedagogical model, given that, there are teachers that promote the rote and repetitive learning, therefore, the didactic process does not respond to the student’s necessities and consequently, they are not relevant to the reality in today’s society. Hence, the general aim is to establish theoretical-methodological guidelines through theoretical references for the use of the constructivist model in the Victoria Vásconez Cuví Educational Unit located in Latacunga city, Cotopaxi. The methodology is based on the interpretive approach, given that, it is interpreted the reality in the educative context; it is delimited in the qualitative research and it follows four stages: preparatory, field work, analytical and informative. The applied method is the inductive, the techniques used were interviews and observations to the teacher and the authority that allowed us to stablish peculiarities of the pedagogical models applied by the institution. As result, it was gotten a document which contains theoretical-methodological guidelines for the application of the constructivist model in the classroom. This document is aimed at the teacher, which constitutes a mean to understand the importance of the student’s interaction in the teaching-learning process using the constructivist model in the didactic process based on participatory strategies and techniques focused on the students, and reflect on student learning.